Sacrifice and Silence Neoliberalism, Right-Wing Populism, and the Repression of Pro-Palestinian Student Movements at Alberta Universities - Wasi, Waniza (Canadian Journal for the Academic Mind, 2025)
This paper explores the intersection of neoliberalism and right-wing populism in the repression of pro-Palestinian student activism at universities, with a focus on the University of Alberta. Since October 2023, students across Canada have mobilized to demand their universities divest from companies complicit in the genocide of Palestinians, disclose financial holdings, defend the right to protest, and condemn the genocide. In response, university administrations, influenced by neoliberal policies and right-wing populist ideologies, have increasingly securitized campuses and relied on police violence to silence dissent. By framing peaceful activism as a threat, institutions sacrifice students’ democratic rights to protect economic interests. This paper explores how the United Conservative Party (UCP) government has influenced the suppression of pro-Palestinian student activism by promoting a right-wing populist narrative that Others pro-Palestinian students and alienates them from the greater campus community. Additionally, this paper criticizes the role of Equity, Diversity, and Inclusion (EDI) initiatives for failing to support genuine systemic change. Ultimately, universities have become complicit in upholding oppressive structures, where dissent is criminalized to protect the neoliberal order.